Coupled dynamic analysis of low and medium speed maglev vehicle-bridge interaction using SIMPACK. (March 2021) - Hu, Junxiong; Ma, Weihua; Luo, Shihui
The low- and medium-speed maglev vehicle generally operates on elevated bridges with a levitation gap of only 8–10 mm, which makes it very sensitive to the vehicle–bridge coupled vibration. To conduct the corresponding modeling and simulation with common dynamics tools, an equivalent processing of the levitation system is required. Using the dynamics software SIMPACK, this paper first introduces the methods of building the multi-body vehicle system, levitation control system and the elastic bridge, respectively, in the SIMPACK railway module, levitation control module and SIMBEAM elastomer module, thus providing a modeling idea for the simulation of the active levitation and operation of low- and medium-speed maglev vehicles through multi-span bridges. It then goes on to simulate and analyze the coupled vibration of a 160 km/h low- and medium-speed maglev vehicle passing through 25 m + 25 m double-span continuous bridges. The research results show that the modeling method introduced in this paper can simulate the low- and medium-speed maglev vehicle–bridge coupled vibration phenomenon, which can be affected significantly by the low-order frequency of the elastic bridge, and can also be intensified under the bridge end impact when the vehicle enters and leaves the bridge. As the running speed of the vehicle increases and the dynamic force increases, the vertical vibration amplitudes of the elastic bridge mid-span, the car body as well as the levitation frame approximate a linear fitting with the vehicle speed. The variation amplitudes of the levitation gap and of the electromagnet current approximate a quadratic fitting with the vehicle speed.